Design of User Interface and User Experience Website-Based Mental Health Applications as a Means of Counseling Universitas Negeri Semarang Students Using Design Thinking Methods and System Usability Scale - Alifia Prastiwi Alifia Prastiwi; Budi Prasetiyo Budi Prasetiyo (Journal of Advances in Information Systems and Technology, 2024)
User Interface (UI) and User Experience (UX) are important components for designing a new application. Website-based online counseling applications are useful for students to conduct online counseling. With the counseling application, students can access counseling without the need to meet directly with a psychologist. To design a counseling application, the right method is needed, namely using design thinking. In addition, the test method used is the System Usability Scale (SUS). Research sampling in the emphatize stage using purposive sampling techniques with predetermined respondent characteristics, 3 people were interviewed participants. From the results of the interview, a user persona and pain point will be created.  Furthermore, at the define stage, the most urgent and significant pain points are identified. At the idea stage, brainstorming ideas that will be used as solutions to problems is carried out. The idea will be implemented into a wireframe. The wireframe that has been created will be developed into a high fidelity design. At the testing stage, sampling uses the random sampling method. The number of respondents to conduct testing was 43 people. The results of the counseling application testing get an SUS score of 75. Interpretation SUS scores occupy grade C in the Good category (good) and get an acceptable predicate in the acceptability range category.